The influence of thinning on the productivity and quality of forest stands in the taiga zone - Y. M. Avdeev; A. E. Kostin; S. M. Khamitova; P. A. Shvetsov (Новые технологии, 2018)
The work deals with assessing the productivity and quality of tree trunks in pine plantations of natural origin under the influence of forestry activities in the Vologda region. The article presents the data of forestry and taxation indicators of forest stand and external convexity of tree trunks. The results can be used to supply data on productivity and quality of tree trunks in forest plantations of pine of natural origin, to simplify the procedure of selection of high-quality tree trunks.